Metamorphic evolution of the Pongomnavolok granulite-enderbite-charnockite complex, Belomorian mobile belt - Наталия Евгеньевна Король; Nataliya Korol (Transactions of the Karelian Research Centre of the Russian Academy of Sciences, 2018)
The geological, petrological and mineralogical characteristics of the multi-stage metamorphic evolution of rocks in the Pongomnavolok granulite-enderbite-charnockite (GEC) complex of the Belomorian mobile belt are discussed and the first attempt to identify and generalize them is made. The GEC complex consists of two intrusive massifs, which intruded under granulite-facies PT-conditions. The first (2728 Ma) Pongomnavolok enderbite-charnockitoid massif with xenoliths and relict mafic granulite – bipyroxeneamphibole crystalline schist units was studied in detail. Two granulite stages, followed by a diaphthoresis stage, are distinguished. The sequence, types and patterns of metamorphic and metasomatic processes and РТ-parameters (TPF, TWQ) characterizing the formation and transformation of the parageneses of mafic granulites and enderbitecharnockitoids under granulite-facies conditions at stage I and their late isofacies recrystallization at stage II of the metamorphic evolution of the GEC complex were studied and analyzed. The detailed study of gabbroids-gabbro-diorites-bipyroxene quartz diorites-granodiorites from the second Pongomnavolok massif showed that they differ from the homonymous intermediate-felsic rocks of massif I in that there is one granulite stage in their metamorphic evolution, as shown by geological, petrological and geochronological (2416 Ma) data. The rock varieties of this massif displayed no signs of isofacies remetamorphism characteristic of stage II, but more recent intensive diaphthoretic alterations have been revealed. At this stage of the study, it is obvious that further investigation, re-thinking and substantiation are needed to prove that both massifs belong to the same GEC complex.